New mental conditioning models for curling sport elite - Bakulev, S. E.; Tajmazov, V. A.; Ashkinazi, S. M.; Kulikov, V. S.; Melnikov, D. S. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to test benefits of two new mental conditioning models for the curling sport elite.